A VALIDATED REVERSED PHASE UHPLC METHOD FOR SIMULTANEOUS ESTIMATION OF ACECLOFENAC AND PARACETAMOL IN BULK AND PHARMACEUTICAL DOSAGE FORM - Bordoloi, Ripunjoy; Baishya, Himakshi; Gogoi, Barnali; Gogoi, Dr. Parthajyoti (Asian Journal of Pharmaceutical Research and Development, 2018)
The purpose of this present work is to develop and validate a simple, linear, accurate and precise reversed phase U-High Performance Liquid Chromatography method for the simultaneous estimation of Paracetamol and Aceclofenac in tablet dosage form (fixed dose combination formulation). For this, the analysis was carried out by High Performance Liquid Chromatography using U-HPLC System (Thermo- Dionex) equipped with an UV detector and stainless steel column (25cm × 4.6mm × 5µm) packed with octadecylsilane chemically bonded to porous silica column. The mobile phase contain buffer , adjusted to pH 7.5 with 1(M) sodium hydroxide and Acetonitrile in the ratio of 60:40 v/v with a flow rate of 1.5 mL/min and detection wavelength 272 nm. The retention time of Paracetamol and Aceclofenac was found to be 1.698 and 2.548 respectively .The method was found to be linear in the concentration range of 10-100 μg/mL for Aceclofenac, 100-500 μg/mL for Paracetamol with correlation coefficient of 0.999 for both drugs respectively. The %RSD of 0.660 and 0.689 for intra-day and 0.897 and 0.856 for inter-day precision, respectively for of Paracetamol and Aceclofenac suggest the precision of the method as all these values are less than 2%. The method has shown good, consistent recoveries for Paracetamol (99.48%) and Aceclofenac (99.42%) which are close to 100%. Thus, the current study showed that the developed reverse-phase liquid chromatography method is sensitive and selective for the estimation of Paracetamol and Aceclofenac in combined dosage form.